A comparative study of public elementary teacher education in the Philippines and in Thailand - Nakpanom, Suwan 1942- (s.n.], 1969)
The purpose of the study is to make a detailed analysis of the education of elementary school teachers in the Philippines and in Thailand with particular reference to the objectives, methods of selection of trainees and curricula.